Phonological Development in Child Language Acquisition: A Study of a Child with Speech Delay - Pipit Agustina; Yana Shanti Manipuspika (Journal of English Language Teaching and Linguistics, 2022)
Children acquire language through interaction with other children, their parents, and their surroundings. Acquisition of language may influence children’s success at school. The language aspect that children acquire first is phonology. In acquiring language, children whose language development is slower than their peers may experience speech delay. Thus, the present study emerges to investigate the phonological development of a three-year-old child who is diagnosed with speech delay as well as to examine the factors that support the development. Using a qualitative approach, this study was a case study that employed a single participant. The results of the study indicated that the participant’s language ability developed significantly after several months of receiving therapy. He displayed an ability to produce imitative sounds and non-imitative ones. The spontaneous utterances were also meaningful compared to what he had before the therapy. The evaluation revealed that the development of the subject was affected by the exposure to language at home. Speech simulation and screen time limitation were keys to improving his language ability